HAEMATOLOGICAL AND BIOCHEMICAL INDICES OF BROILER CHICKENS FED GINGER (ZINGIBER OFFICINALE) BASED DIETS - Ebegbulem, V. N. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2018)
An experiment was conducted using 150 day-old broiler chicks (Anak 2000 strain) to determine the effect of feeding graded levels of ginger-based diets on their haematology and serum biochemical indices. Five (5) experimental diets containing 0, 2, 4, 6 and 8% ginger designated as T1, T2, T3, T4 and T5 respectively, were formulated and fed to the birds for a period of 8 weeks. Diet T1 served as the control. Haematology and serum biochemical assays were carried out at the end of the experiment. Proximate analysis of the test ingredient (ginger) showed that it is composed of crude protein (5.84%), crude fibre (2.9%), ether extract (1.35%), ash (1.79%) and nitrogen free extract (88.10%). Results showed that the serum cholesterol content of the birds (range of 105.72 to 123.61mg/dl) significantly (P< 0.05) declined with increasing percentage inclusion of ginger in the diets, while creatinine and urea contents increased simultaneously with increased percentage ginger inclusion. Birds on T5 had significantly (P<0.05) highest serum cholesterol, glucose and creatinine content, but least in serum total protein and globulin content. All haematological indices of the birds were not significantly (P>0.05) affected by dietary treatments. The research confirmed the hypo-cholesterol action of ginger on broiler chickens. It was concluded that ginger can be included up to 6% in the diet of broiler chickens without compromising their physiological status.